Realizing strong photon blockade at exceptional points in the weak coupling regime - Zigeng Li; Xiaomiao Li; Guofeng Zhang; Xiaolan Zhong (Frontiers in Physics, 2023)
We theoretically prove that it is possible to realize strong photon blockade at n-order exceptional points (EPn) in a two-level quantum emitter (QE)–cavity quantum electrodynamics (QED) system even if the emitter–cavity coupling strength is weak. When the single-mode cavity is gain, we show that the ultrastrong single-photon blockade (1 PB) emerges at two-order exceptional points (EP2), avoiding the strong non-linearity of the system. In addition, we first give the pseudo-Hermitian condition for the non-Hermitian cavity QED system and find that the third-order exceptional points (EP3) can be predicted under certain constraints of the parameters. For this case, the pronounced 1 PB at EP3 will be triggered. Furthermore, we also consider the usual EP2-enhanced 1 PB existing in the system with or without the dipole–dipole interaction (DDI) under the pseudo-Hermitian condition. A striking feature is that the system without DDI can realize more obvious 1 PB at EP2 than the case of with DDI. What is important is that both EP2 and EP3 will appear in the weak coupling regime. Our proposal sheds new light on strong EP-engineered photon blockade in the weak coupling regime, providing a unique platform for making high-quality single-photon sources.